If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3/4)x=(5/8)
We simplify the equation to the form, which is simple to understand
(3/4)x=(5/8)
Reorder the terms in parentheses
( + 0.75x)=( + 0.625)
Remove unnecessary parentheses
+ 0.75x=( + 0.625)
Remove unnecessary parentheses
+ 0.75x=0.625
We move all terms containing x to the left and all other terms to the right.
+ 0.75x=0.625
We simplify left and right side of the equation.
+ 0.75x=0.625
We divide both sides of the equation by 0.75 to get x.
x=0.83333333333333
| 4(5x-7)=56 | | X+1+1=6x-5x+2 | | .40x+.1=.60 | | N=-300+15N | | 5a+2+2a-7+4a=7 | | 6z+19=4z+19 | | -5x-2-10=2-(x+4) | | 85l=685 | | 3(X+1)=2X+24-X | | -3(y-7+3)+3=0 | | 6g+4(g)=1-g | | -x+x=91+7 | | X=-7y-10 | | -2x-6=-2x-4 | | 2.39=x-40 | | 10+9C+5C*2-4+6C= | | a-2-2+15=1+3a | | 49h+20=314 | | -2x-6=-2-4 | | 4p+2+2p+1=8 | | -5x+9=17-x | | 6y=8x-10 | | 10t^2=12t+23 | | C+c=73 | | -3(-4-6y)+7(y+5)= | | 75+2x=0-15 | | 4+x=200 | | 4x^2+4x+32=0 | | 4x+1+3x=-3 | | 2x^2+3+3=-7x | | Y=2x+(-8) | | -15x+9=17-x |